Integration of Ethnopedagogy in the P5 Module Based on Besutan Art as a Medium for Preserving Jombang Culture - Anggraeni, Kiki Hapsari; Hendratno, Hendratno; Sukartiningsih, Wahyu (Papanda Publisher, 2025)
This study aims to explore and develop a Pancasila Student Profile (P5) learning module based on Kesenian Besutan, a traditional art form from Jombang, through the integration of ethnopedagogical principles. Using a mixed methods approach, the research combines qualitative data from interviews with cultural practitioners, classroom observations, and document analysis with quantitative data from expert validation of the developed module. The goal is to preserve local culture while simultaneously cultivating students’ character in line with Pancasila values. The qualitative findings revealed that Besutan carries deep historical and philosophical meaning related to the Indonesian struggle for independence and local wisdom, making it a strong foundation for cultural-based learning. Quantitative validation from education experts and cultural figures resulted in an average score of 91.67, indicating the module is